DAMPAK DIGITALISASI TERHADAP MODEL BISNIS KEWIRAUSAHAAN PADA SEKTOR E-COMMERCE - Ari Prabowo; Sri Rahayu; Sundjoto, Sundjoto; Rifda Fitrianty (LPSDI Bina Patria, 2025)
Digitalization has emerged as the primary driver of transformation in the e-commerce sector, significantly affecting entrepreneurial business models. This study aims to examine the impact of digitalization on entrepreneurial business models within the e-commerce sector by utilizing secondary data through literature reviews and content analysis. The research focuses on the implementation of e-commerce platforms, digital marketing, data analytics, and operational automation, which collectively drive operational efficiency, product innovation, and enhanced customer relationships. The findings indicate that the adoption of digital technology positively influences the transformation of entrepreneurial business models, as digital features help entrepreneurs improve speed, accuracy, and flexibility in business operations. Moreover, the study identifies challenges faced by business operators, such as data security issues, limited digital skills, and increasingly intense market competition. The implications of these findings are both theoretical and practical, offering strategic recommendations for entrepreneurs and policymakers to optimize the use of digital technology to enhance competitiveness and economic growth in the digital era.